Structural and magnetic properties of mono-dispersed iron carbide (FexCy) nanoparticles synthesized by facile gas phase reaction. Issue 8 (1st June 2019) - Wang, Yinwei; Liu, Shoufa; Huang, Pengfei; Xie, Huan; Qiao, Xun
Abstract: Iron carbide (Fe-C) nanoparticles with different atomic compositions were synthesized by a gas phase reaction. The particle morphology and size distribution were characterized by TEM, and the elemental distributions were determined by EDX. The crystal structures were measured by XRD, and the surface chemical states of the as-synthesized nanoparticles were confirmed by XPS. The magnetic property measurement showed that the iron carbide nanoparticles presented higher magnetization when the iron atomic percentage was higher. The stability testing showed that the iron carbide nanoparticles with higher iron atomic percentage had a lower air-stability.